2018
DOI: 10.3390/ma11101918
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Selective Laser Melting to Increase the Performance of AlSi9Cu3Fe Alloy

Abstract: For the first time, the comprehensive characterization of the additively manufactured AlSi9Cu3Fe alloy is reported in this paper. Conventionally, the AlSi9Cu3(Fe) alloy is prepared by high-pressure die casting (HPDC), but this technology largely does not offer such opportunities as additive manufacturing (AM) does, especially in the design of new lightweight parts. In the present paper, testing samples were prepared by selective laser melting (SLM), one of the AM technologies, and characterized in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…That is, a material which has a good strength-ductility balance can be produced by using SLM. Similar results have been reported in previous studies and have been explained by the microstructure specific to SLM [11,30]. Using SLM with the Base alloy did not dramatically increase the high-temperature strength; however, the Base + 3Fe and Base + 5Fe alloys were strengthened by SLM because of the addition of Fe.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…That is, a material which has a good strength-ductility balance can be produced by using SLM. Similar results have been reported in previous studies and have been explained by the microstructure specific to SLM [11,30]. Using SLM with the Base alloy did not dramatically increase the high-temperature strength; however, the Base + 3Fe and Base + 5Fe alloys were strengthened by SLM because of the addition of Fe.…”
Section: Resultssupporting
confidence: 90%
“…That is, a material which has a good strength-ductility balance can be produced by using SLM. Similar results have been reported in previous studies and have been explained by the microstructure specific to SLM [11,30]. The UTS and the EL at 300 °C of the sample prepared in this study and the novel cast Al alloys recently reported [25][26][27][28] are summarized in Table 3.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These include casting alloys like AlSiCu alloys (EN AC-46xxx and EN AC-47xxx). These alloys offer high tensile strengths of up to 500 MPa with a low elongation at break of 5% [5][6][7].Many known alloys are difficult to process by laser powder bed fusion due to the formation of pores and cracks during solidification. These include medium and high strength wrought alloys of the alloy systems AlCu (EN AW-2xxx) [8][9][10], AlMgSi (EN AW-6xxx) [11,12], and AlZnMg (EN AW-7xxx) [13][14][15].…”
mentioning
confidence: 99%
“…These include casting alloys like AlSiCu alloys (EN AC-46xxx and EN AC-47xxx). These alloys offer high tensile strengths of up to 500 MPa with a low elongation at break of 5% [5][6][7].…”
mentioning
confidence: 99%